Le Corbusier / architect and feminist - Samuel, Flora (Chichester, West Sussex, England : TascWiley-Academy, 2004)
This book will cover Le Corbusier's upbringing and training, both of which were formative in his adoption of the principles which influenced his architecture and art. Examining his opinions and style, it will set these in the context of the architectural and general cultural atmosphere of his time, covering issues of gender and religion.
Acknowledgements. List of Illustrations. Illustration Credits. Preface. Introduction. PART ONE: REAL. Chapter 1. Intimate Relationships. Marie Charlotte Amelie Jeanneret-Perret: his mother. Yvonne Gallis: his wife Intimate Relations Josephine Baker * Marguerite Tjader Harris * Minette De Silva. Conclusion. Chapter 2. Professional Relationships. Women Abroad. Women at Work. Little Paris Birds * Married women * Women Writers. Women Clients. Villa Meyer * Villa Stein de Monzie * Maison de Mandrot * Heidi Weber House. Summary. Women Collaborators. Le Corbusier's 'best propagandists' * Intellectual support. Women Designers. Charlotte Perriand * Eileen Gray * Jane Drew. Conclusion. Chapter 3. Feminism, fashion and physical culture. Feminism in France at the beginning of the twentieth century. Feminism and Physic al Culture. The Anti-Corset league * Dance * Sport. Fashion. Fashionable society * Paul Poiret and the development of a new feminine aesthetic * Male adornment * Fashion magazines * Fashion and furniture. Conclusion. PART TWO: IDEAL. Chapter 4. Orphism and the quest for harmonious unity. Origins of Le Corbusier's interest in Orphism. Catharism * Rabelais and Cervantes * Education and Self-Education * Synthesis. Orphism. Pythagoras * Plato and the Union of Opposites * Alchemy * Pico della Mirandola * Summary. Orphism and the questioning of sexual roles in Early Twentieth Century Paris. Josephin Peladan * Guillaume Apollinaire * Andre Breton and the Surrealists * Jean Cocteau * Summary. Conclusion. Chapter 5. Women in the art of Le Corbusier Tools of Unity. Symbolism. The exploitation of physical response in the pursuit of spiritual change * Geometry * Colour. The artistic representation of women in Le Corbusier's milieu. Women of the East. The emergence of the numinous woman in Le Corbusier's painted work. Union of Opposites. Woman and the sea * Woman and the shell * Woman and music * All seeing woman * Ubu * La cathedrale de Sens * Siren * Taureau/Icone. The Poem of the Right Angle 1947-1953. Sun and water, man and woman * Flesh * Fusion: male and female * Fusion: Body and Spirit * Woman and enlightenment * Mary * Love. Conclusion. Chapter 6. The cult of woman and the religious architecture of Le Corbusier. La Sainte Baume. Background to the project * The site * Mary Magdalene * The Basilica * Permanent City * The Museum * The Theatre * The Park * Summary. Ronchamp. Building and Body * The Ear * The Vase * The Marys * East Door * Summary. Conclusion. Chapter 7. Sexual Harmony and the Urbanism of Le Corbusier. Sex and Planning. The Radiant City. The spiritual home incarnate. Conclusion. Conclusion. Selected Bibliography. Index.
Keywords: Le Corbusier, -- 1887-1965; Architects -- France; Architecture, Modern -- 20th century; Feminism and architecture